3D scanning electron microscopy applied to surface characterization of fluorosed dental enamel. (May 2016) - Limandri, Silvina; Galván Josa, Víctor; Valentinuzzi, María Cecilia; Chena, María Emilia; Castellano, Gustavo
Highlights: High resolution stereo pairs from fluorotic teeth were acquired in SEM. Height maps and bearing area curves were obtained from these SEM stereo images. Surface roughness was characterized assessing functional and amplitude parameters. Stereomicroscopy proved to be a useful tool to study the roughness on these samples. Abstract: The enamel surfaces of fluorotic teeth were studied by scanning electron stereomicroscopy. Different whitening treatments were applied to 25 pieces to remove stains caused by fluorosis and their surfaces were characterized by stereomicroscopy in order to obtain functional and amplitude parameters. The topographic features resulting for each treatment were determined through these parameters. The results obtained show that the 3D reconstruction achieved from the SEM stereo pairs is a valuable potential alternative for the surface characterization of this kind of samples.